The effects of disagreement, interference, negative emotion on the transference of conflict - Lee, Seunghoo; Suh, Yongwon (Korean Journal of Industrial and Organizational Psychology, 2015)
The purpose of this research is examination of the effects of disagreement, interference, negative emotion on task conflict and relationship conflict based on the assumption that interpersonal conflict is a combination of cognitive, behavioral, affective components. In addition, the research attempts to show that the effects of behavioral and affective components of conflict on relationship conflict are vary with the individual's value orientation. Furthermore, the investigation that these components of conflict have impact on individual's creative performance was made. 141 participants were randomly assigned to three experimental conditions (disagreement, interference, negative emotion) and engaged in group brain- storming session while experimenter manipulated the group interaction according to each condition. Findings showed that the creative performance was highest when there is only disagreement in the setting of conflict situation, while interference and negative emotion decrease the creative performance. Task conflict was not affected by interference, but increased by negative emotion. Relationship conflict was increased by inclusion of components of conflict in a linear trend. Negative emotion had greater effect on relationship conflict when an individual had collective value orientation. The limitation and implication of the study and direction of future research were discussed.